2015
DOI: 10.1007/s10900-015-0131-0
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Products and Dietary Supplements: A Cross-Sectional Survey of Use, Attitudes, and Knowledge Among the Lebanese Population

Abstract: There has been a marked increase in use of herbal products and dietary supplements (HP/DS) in many developed and developing countries. However, data about consumption patterns and awareness about these products in the Lebanese population is scarce. The present study aimed to examine the determinants of HP/DS use in Lebanese adults, identify potential interactions and safety concerns and assess the knowledge and attitudes of consumers towards the efficacy and safety of these products. A face-to-face, 28-item su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
45
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 28 publications
10
45
2
4
Order By: Relevance
“…Female gender, higher level of education and preferring herbal drugs compared to the other medicines were shown as factors determining the use of herbal drugs. Our results are partially compatible with the results of other authors (13)(14). In the study conducted in Lebanon (13) it was shown that the use of herbal drugs and dietary supplements was associated with female gender, but also with increasing age.…”
Section: Table 2 Crude and Adjusted Odds Ratio For Characteristics Asupporting
confidence: 93%
See 1 more Smart Citation
“…Female gender, higher level of education and preferring herbal drugs compared to the other medicines were shown as factors determining the use of herbal drugs. Our results are partially compatible with the results of other authors (13)(14). In the study conducted in Lebanon (13) it was shown that the use of herbal drugs and dietary supplements was associated with female gender, but also with increasing age.…”
Section: Table 2 Crude and Adjusted Odds Ratio For Characteristics Asupporting
confidence: 93%
“…Despite all this, the vast majority of our patients who use herbal preparations did not experience any inconvenience during the use of herbal remedies A great problem in self-medication with herbal drugs is the fact that the patients consider that the herbal preparations are completely safe and therefore they prefer to use them at the expense of conventional drugs (9). Approximately 70% of our patients showed such attitude towards use of herbal drugs, which is in accordance with the results of authors in Malaysia (12) and Lebanon (13). It is particularly interesting that, despite the significant sociological and cultural differences between patients who participated in our study and patients in Malaysia and Lebanon, the attitude towards herbal medicines is similar.…”
Section: Table 2 Crude and Adjusted Odds Ratio For Characteristics Asupporting
confidence: 88%
“…There have been several surveys in the past demonstrating consumers' opinions about the safety of herbal medicines [911]. According to surveys of Serbia [9] and Saudi Arabia [10], 73.3% (211) of Serbian respondents and 81.2% (239) of Saudi Arabian respondents considered that the use of herbal medicines and herbal dietary supplements is harmless, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…According to surveys of Serbia [9] and Saudi Arabia [10], 73.3% (211) of Serbian respondents and 81.2% (239) of Saudi Arabian respondents considered that the use of herbal medicines and herbal dietary supplements is harmless, respectively. Meanwhile, only 12.1% (88) of Lebanese respondents perceived that herbal products sold in Lebanon are pure [11]. …”
Section: Discussionmentioning
confidence: 99%
“…El porcentaje de uso (59,5%) está por encima de lo reportado por encuestas nacionales en USA (17,7%) (33) , e Irán (38,6%) (34) , y por debajo de un estudio previo en Panamá (73,7%) (35) . Cabe destacar que el 27,9% de los pacientes en consulta externa habían usado plantas medicinales como tratamiento previo al uso de medicina convencional; sin embargo, este dato no suele ser indagado en la práctica diaria, a pesar que estudios anteriores (36,37) ya recomiendan la importancia de integrar el tratamiento convencional con el objetivo de mejorar la adherencia y evitar posibles efectos adversos e interacciones medicamentosas.…”
Section: Discussionunclassified